Tunable Plasmon Resonance of a Touching Gold Cylinder Arrays (Journal of Atomic and Molecular Sciences, 2012)
We investigate the plasmon resonance of a touching gold cylinder arrays surrounded with air or dielectric. We show that the plasmon resonance is tunable by modulating the cylinder radius, the cylinder layer and refractive index of the dielectric. It is found resonance peak blue-shifts and splits as the gold cylinder radius reduces, width of the resonance peak gets much smaller as layer increases, and resonant peak red-shifts noticeably as dielectric refractive index increases. Based on electric field distributions at the resonance wavelengths we reveal the mechanism of the transmission enhancement. These phenomena are helpful for the design of potential optics devices.